Interferon gamma release assays for monitoring the response to treatment for tuberculosis: A systematic review. Issue 6 (December 2015) - Clifford, Vanessa; He, Yu; Zufferey, Christel; Connell, Tom; Curtis, Nigel
Summary: Introduction: The ability to monitor the response to therapy for tuberculosis (TB) and confirm adequate treatment would be a major advance. The utility of interferon gamma assays (IGRA) for this purpose remains uncertain. Methods: A systematic search of all studies investigating commercial IGRA to monitor anti-tuberculous treatment was done. Studies were included if they included an IGRA before the start of, and at least once during, treatment for active or latent TB. Results: We identified 30 studies, of which 24 used QuantiFERON-TB (QFT), three used T-SPOT. TB and three used both QFT and T-SPOT. TB . Most studies were done in low TB incidence countries. No uniform pattern was seen in IGRA conversion and reversion rates at the end of treatment for active or latent TB. In most studies, the majority of IGRA results remained positive at the end of treatment. In many studies, the quantitative levels of IFN-γ decreased during treatment, particularly in active TB. There was significant heterogeneity in the included studies. Conclusion: While quantitative IGRA responses generally fall during treatment for TB, the large degree of variation in results between participants in each study means that IGRAs are unlikely to be useful for monitoring anti-tuberculous treatment in clinical practice for any individual patient.